Answer:
r = t - u - s
Step-by-step explanation:
To solve for r in terms of s, t, and u, means to have r on one side and have t, u, and s.
t = u - s + r
t - u = s + r
t - u - s = r
Answer:
option B
(−1, 0) and (0, 6)
Step-by-step explanation:
Given in the question two equations,
Equation 1
y =−x² + 5x + 6
Equation 2
−6x + y = 6
plug value of y in second equation
−6x −x² + 5x + 6 = 6
-x² -6x + 5x +6 - 6 = 0
-x² - x + 0 = 0
-x² -x = 0
-x(x+1) = 0
x = 0
and
x = -1
plug value of x in second equation to find y
x = 0
−6(0) + y = 6
0 + y = 6
y = 6
and
x = -1
−6(-1) + y = 6
6 + y = 6
y = 0
Ok so you do 900 ÷ 10 which = 90 and 90 x 10 = 900 so the answer is 90